2019
DOI: 10.1038/s41598-019-45969-4
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of endocannabinoids in the brain by synthetic cannabinoid JWH-018: mechanism and effect on learning and memory

Abstract: The impairment of learning and memory is a well-documented effect of both natural and synthetic cannabinoids. In the present study, we aimed to investigate the effect of acute administration of JWH-018, a synthetic cannabinoid, on the hippocampal metabolome to assess biochemical changes in vivo . JWH-018 elevated levels of the endocannabinoids, anandamide (AEA) and 2-arachidonoylglycerol (2-AG). The increase of endocannabinoid levels in response to JWH-018 could be inhibited by co-admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…Our in vitro electrophysiological analysis in brain slices of mice treated with JWH-018 revealed an impairment in LTP. Previous studies revealed that a single JWH-018 administration induced an impairment in short-(2 h) and longterm (24 h) working memory in mice (Barbieri et al, 2016;Barbieri et al, 2022;Li et al, 2019), in line with preclinical studies demonstrating amnesic properties of either natural or SCBs. These alterations have been associated with CB 1 receptor activation and with the ability of the drug to disrupt hippocampal LTP (Barbieri et al, 2016;Barbieri et al, 2022;Hoffman et al, 2017), although treatment with JWH-018 does not substantially modify the synaptic excitability.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Our in vitro electrophysiological analysis in brain slices of mice treated with JWH-018 revealed an impairment in LTP. Previous studies revealed that a single JWH-018 administration induced an impairment in short-(2 h) and longterm (24 h) working memory in mice (Barbieri et al, 2016;Barbieri et al, 2022;Li et al, 2019), in line with preclinical studies demonstrating amnesic properties of either natural or SCBs. These alterations have been associated with CB 1 receptor activation and with the ability of the drug to disrupt hippocampal LTP (Barbieri et al, 2016;Barbieri et al, 2022;Hoffman et al, 2017), although treatment with JWH-018 does not substantially modify the synaptic excitability.…”
Section: Discussionsupporting
confidence: 72%
“…The tail suspension test (TST) is one of the most widely used models for assessing antidepressant‐like behaviours in mice. It was suggested in many studies that the endocannabinoid system, in particular the cannabinoid receptors (CB 1 and CB 2 ) play a significant role in the pathophysiology of depression and stress/anxiety disorders (Li et al, 2019; Maldonado et al, 2020; Poleszak et al, 2020; Smaga et al, 2017). We investigated in a previous study the acute effects of Δ9‐THC and JWH‐018 and its halogenated derivatives on the tail suspension test as a first investigation to reveal their possible actions in affecting stress/anxiety in mice, as suggested by literature (Barbieri et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…A decrease in BDNF following JWH-018 treatment was observed in the hippocampus. As previously mentioned, the neurotrophic factor BDNF plays an important role in modulating the learning and memory process, promoting neurogenesis, synaptogenesis [ 109 ], and the alteration of BDNF levels after JWH-018 exposition, which may explain its negative effect on memory performance. Nevertheless, this effect on BDNF release observed with JWH-018 is in contradiction with the effect reported previously with THC administration, where an increased BDNF production was observed.…”
Section: Cannabinoids and Endocannabinoid Systemsmentioning
confidence: 99%
“…The abuse liabilities of THC and synthetic cannabinoids are usually attributed to their influence on CB 1 receptors expressed in the VTA and NAC, which are major brain regions associated with the development of addiction-related behaviors ( Nestler, 2001 ). Cannabinoids may also affect the expression of CB 2 receptors ( Sun et al, 2017 ), along with enzymes that degrade endocannabinoids ( Li et al, 2019 ). Thus, we measured the mRNA levels of endocannabinoid-related genes in the VTA and NAC of mice repeatedly treated with JWH-018.…”
Section: Resultsmentioning
confidence: 99%